Maternal Near Miss Morbidity and Maternal Mortality in a Tertiary Referral Center in Turkey - Dilek Uygur; Yaprak Engin Üstün; Özgür Kara; Kudret Erkenekli; Selcen Yüksel; Salim Erkaya; Sema Sanisoğlu; Nuri Danışman; Aykan Yücel (Medical Network, 2017)
Objective: The objective of the study is to present the maternal near miss and maternal mortality cases from a tertiary hospital and to evaluate the factors associated with the presence of maternal near miss. Study Design: We performed a retrospective study, including all women who fulfilled the WHO criteria for maternal near miss or death between June 2009 and June 2014 at a tertiary referral education hospital. This study was conducted to evaluate the risk factors' influence on near miss, multivariate logistic regression was used. Before setting logistic regression, univariate analyses were used to select candidate variables. Results: During the 5-year study, there were 82924 deliveries and 81673 live births. We identified 202 maternal near miss events and 11 maternal deaths. The maternal near miss ratio was 2.47 per 1.000 live births and the maternal mortality ratio was 13.46 per 100.000 live births. There were 213 women with a severe maternal outcome ratio (SMOR) (near miss + maternal death), with a ratio of 2.6 cases/1.000 live birth. Near miss events were associated with length of hospital stay (p<0.001), hemoglobin level (p=0.003). Conclusion: By the help of the WHO near miss approach, we identified that near miss events were associated with length of hospital stay, hemoglobin level, cesarean section deliveries and parity.